2019
DOI: 10.1016/j.jadohealth.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Racial Discrimination and Acute Physiological Responses Among Black Young Adults: The Role of Racial Identity

Abstract: Purpose: Racial discrimination has long-term consequences for cardiovascular health, potentially by dysregulating acute physiological responses. However, the role of psychological factors that may be protective or increase vulnerability for dysregulated responses, such as racial identity, remains unclear. This study examines the association between racial discrimination and acute parasympathetic responses, and the role of racial centrality, private regard, public regard in this association. Methods: Black youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 39 publications
1
44
3
Order By: Relevance
“…For members of the Detached subgroup, limited access to and use of culturally-relevant coping strategies in the face of multifaceted stressors could engender feelings of hopelessness. Of note, in prior research, the findings on racial centrality have been mixed; some studies have indicated that low centrality may lead to poorer outcomes whereas other work has suggested that lower racial centrality may buffer individuals from being personally affected by society’s negative perceptions of Black individuals and thus protected against adverse health (Volpe et al, 2019). Although additional research is required to shed light on these interrelations, our findings complement the literature by demonstrating how individuals with the lowest centrality may be at greater risk for suicidal behavior and its correlates compared to those with higher centrality, who are at relatively lower risk.…”
Section: Discussionmentioning
confidence: 99%
“…For members of the Detached subgroup, limited access to and use of culturally-relevant coping strategies in the face of multifaceted stressors could engender feelings of hopelessness. Of note, in prior research, the findings on racial centrality have been mixed; some studies have indicated that low centrality may lead to poorer outcomes whereas other work has suggested that lower racial centrality may buffer individuals from being personally affected by society’s negative perceptions of Black individuals and thus protected against adverse health (Volpe et al, 2019). Although additional research is required to shed light on these interrelations, our findings complement the literature by demonstrating how individuals with the lowest centrality may be at greater risk for suicidal behavior and its correlates compared to those with higher centrality, who are at relatively lower risk.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived racial discrimination has been consistently linked with stress and disparities in health and illness experiences [ 5 , 36 , 54 ]. For instance, psychological, physiological, and cognitive reactions to experiences of racial discrimination are precursors of mental and physical health problems among individuals who perceive such discrimination [ 15 , 19 , 58 ]. Furthermore, perceptions of racial/ethnic discrimination among racial minority groups is associated with general self-reported poor health, as well as socioemotional distress resulting in substances use, sexual intercourse without the use of adequate protective tools, suicidal thoughts and attempts [ 33 , 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…This ability to disregard dehumanizing perceptions of African Americans as personally relevant may have certain health benefits for African Americans. For instance, lower levels of racial centrality has been found to mitigate the relationship between racial discrimination and physiological indicators of health (Volpe et al, 2019). Taken together, while racial centrality may be protective in some instances, it may also increase negative consequences in the face of race-related threats because of greater connection between the self and the racial group.…”
Section: Figure 2 Association Between Depressive Symptoms and Metadehumanization (Hypothesis 3b)mentioning
confidence: 99%